Formation of Dianions in Helium Nanodroplets1. Issue 50 (8th October 2014) - Mauracher, Andreas; Daxner, Matthias; Huber, Stefan E.; Postler, Johannes; Renzler, Michael; Denifl, Stephan; Scheier, Paul; Ellis, Andrew M.
Abstract The formation of dianions in helium nanodroplets is reported for the first time. The fullerene cluster dianions (C60)n2− and (C70)n2− were observed by mass spectrometry for n≥5 when helium droplets containing the appropriate fullerene were subjected to electron impact at approximately 22 eV. A new mechanism for dianion formation is described, which involves a two‐electron transfer from the metastable He− ion. As well as the prospect of studying other dianions at low temperature using helium nanodroplets, this work opens up the possibility of a wider investigation of the chemistry of He−, a new electron‐donating reagent.